Study on The Efficacy of Nitrogen Utilization by Rice Genotypes Part 1: Clustering and Selection for Rice Genotypes - Darjanto Darjanto; Didik Indradewa; Bostang Radjagukguk; Taryono Taryono (Fakultas Biologi | Universitas Jenderal Soedirman, 2011)
This experiment was carried out in a greenhouse as, the first part of four consecutive experiments. Sixty rice genotypes comprising 30 national and 30 local genotypes were evaluated for their responses and efficacy to nitrogen (N, urea) fertilizer application. Two levels of N fertilizer, i.e., 0 (N1) and 120 (N2) kg of N per hectare were applied. Randomized Block Design (RBD) with three replications was used as the experimental design. The observed parameters were grain yield per pot and grain yield index (GI). Based on average of grain yield of N1, average of grain yield of N2, and grain yield index (GI), the 60 evaluated genotypes were classified into four clusters. These clusters consisted of 26 efficient and responsive (ER) genotypes, 7 efficient and non-responsive (ENR) genotypes, 6 non-efficient and responsive (NER) genotypes, and non-efficient and non-responsive (NENR) genotypes. Replacement of cultivars in rice cultivation, from non efficient (NE)-genotype to efficient (E)-genotype has a potential of yield increase of 90.83%, replacement of non-responsive (NR) with responsive (R) genotype has a potential yield increase of 59.57%, replacement of local genotypes with national genotypes has a potential to increase yield 8.66% only. Of the 26 ERs, genotypes with the highest efficiency were Singkil, IR-66, Indragiri, Sintanur, and Widas. Genotypes with the highest response were Ciliwung, IR-66, Ciherang, Sintanur, and Cisadane. These genotypes can be used to increase rice production, to reduce production costs and to reduce environmental pollution. The ER, ENR and NER genotypes can be used as parents in breeding for high yielding and N efficient rice genotypes.